2016
DOI: 10.1016/j.jaci.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Blood lipid levels associate with childhood asthma, airway obstruction, bronchial hyperresponsiveness, and aeroallergen sensitization

Abstract: The blood lipid profile is associated with asthma, airway obstruction, bronchial responsiveness, and aeroallergen sensitization in 7-year-old children. These findings suggest that asthma and allergy are systemic disorders with commonalities with other chronic inflammatory disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 44 publications
1
45
1
Order By: Relevance
“…Yet there was also evidence that the metabolomic profile for AHR, a composite variable incorporating airflow obstruction, hyper-responsiveness, and inflammation, included aspects distinct from the FEV 1 /FVC signatures, which reflect mainly airflow obstruction. The majority of the AHR-associated metabolites were polar and non-polar lipids, in agreement with previous evidence demonstrating altered lipid profiles in asthmatics [25]. Succinate, Alanine and Phenyalanine which have been reported to be associated with asthma and asthma related outcomes in multiple studies and multiple biological media [13] were only significantly associated with FEV 1 /FVC.…”
Section: Discussionsupporting
confidence: 88%
“…Yet there was also evidence that the metabolomic profile for AHR, a composite variable incorporating airflow obstruction, hyper-responsiveness, and inflammation, included aspects distinct from the FEV 1 /FVC signatures, which reflect mainly airflow obstruction. The majority of the AHR-associated metabolites were polar and non-polar lipids, in agreement with previous evidence demonstrating altered lipid profiles in asthmatics [25]. Succinate, Alanine and Phenyalanine which have been reported to be associated with asthma and asthma related outcomes in multiple studies and multiple biological media [13] were only significantly associated with FEV 1 /FVC.…”
Section: Discussionsupporting
confidence: 88%
“…To the Editor Extensive studies support the presence of links between dyslipidemia and allergic diseases, and there has been with particular emphasis on allergen sensitization, 1-3 asthma, 2,4 and atopic dermatitis (AD). Although evidence supporting a link of allergic rhinitis (AR) with dyslipidemia is limited and controversial, 2,3 many researchers have focused on the relationship of obesity and rhinitis, rather than blood lipids.…”
mentioning
confidence: 99%
“…To the Editor, Being small for gestational age (SGA) is associated with significant perinatal outcomes, such as foetal and neonatal distress, and longterm complications, such as insulin resistance and cardiovascular disease. 1,2 Maternal history of chronic diseases such as hypertension can be a risk factor for being SGA. 3 Asthma is one of the most frequent chronic diseases encountered during pregnancy, and Murphy et al 4 reported that maternal asthma was associated with an increased risk of SGA in their systematic review.…”
mentioning
confidence: 99%
“…Although it must be underlined that this study reported a critical bias (asthma diagnosis was based exclusively on a questionnaire), this limitation did not affect the validity of the serum HDL levels at baseline and follow-up. This limit was overcome in the study performed by Vinding et al [42], who conducted research in the Copenhagen Prospective Studies on Asthma in Childhood2000 at-risk birth cohort, and noted significant associations between lipid levels and clinical outcomes. In particular, LDL and TG levels were associated with concurrent asthma and airway obstruction, assessed by spirometric parameters and fraction of exhaled nitric oxide (FeNO) levels.…”
Section: Resultsmentioning
confidence: 99%